2009
DOI: 10.1002/eji.200939709
|View full text |Cite
|
Sign up to set email alerts
|

Thymocyte deletion can bias Treg formation toward low‐abundance self‐peptide

Abstract: Autoreactive CD4 1 T cells can undergo deletion and/or become CD25 1 Foxp3 1 Treg as they develop intrathymically, but how these alternative developmental fates are specified based on interactions with self-peptide(s) is not understood. We show here that thymocytes expressing an autoreactive TCR can be subjected to varying degrees of deletion that correlate with the amount of self-peptide. Strikingly, among thymocytes that evade deletion, similar proportions acquire Foxp3 expression. These findings provide evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 53 publications
(70 reference statements)
2
12
0
Order By: Relevance
“…There was a significant decrease in the number of 6.5 + CD4SP thymocytes in TS1xHA28 mice relative to TS1 mice, but the number of 6.5 + CD4SPFoxp3 + thymocytes was significantly increased, consistent with previous studies showing that the presence of the self-HA can induce both 6.5 + CD4SP thymocyte deletion and 6.5 + CD4SPFoxp3 + thymocyte formation in TS1xHA28 mice (9, 12) (Fig. 1C).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…There was a significant decrease in the number of 6.5 + CD4SP thymocytes in TS1xHA28 mice relative to TS1 mice, but the number of 6.5 + CD4SPFoxp3 + thymocytes was significantly increased, consistent with previous studies showing that the presence of the self-HA can induce both 6.5 + CD4SP thymocyte deletion and 6.5 + CD4SPFoxp3 + thymocyte formation in TS1xHA28 mice (9, 12) (Fig. 1C).…”
Section: Resultssupporting
confidence: 91%
“…In HA28 mice, the SV40 early region promoter/enhancer drives expression of a truncated polypeptide corresponding to the NH 2 -terminal 273 amino acids of the PR8 HA polypeptide, and studies using bone marrow chimeras have shown that this polypeptide is expressed in radioresistant cell types (9, 12, 29, 33, 34). By contrast, the I-E a MHCII promoter directs transgene expression in HACII mice, and flow cytometric studies have demonstrated cell surface expression of the HA selectively by MHC Class II+ cells (35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A very similar trend was observed by Cozzo Picca et al [17] using TCR transgenic cells specific for an epitope of influenza virus in the presence of different levels of expression of this agonist. Atibalentja et al [18] also observed this trend following intravenous injection of varying concentrations of hen egg-white lysozyme (HEL), which was rapidly processed and presented in the thymus, resulting in the negative selection of specific TCR transgenic T and an increase in TCR transgenic T at low, but loss at higher, HEL concentrations.…”
Section: Methodssupporting
confidence: 82%
“…TCR/model antigen transgenic systems showed that T reg cell differentiation, similar to clonal deletion, can be instructed by TCR agonists (2, 3), and this was later confirmed for polyclonal T cells and natural self-antigens (4). In some models, low antigen levels favored T reg cell generation, whereas high antigen doses favored deletion, suggesting that T reg cell differentiation occurs within an avidity window between positive selection and deletion (58). Other observations, however, are difficult to reconcile with a reductionist, purely signal strength-based model.…”
mentioning
confidence: 99%